Exploration of Lichenized fungi in Tea Gardens of Assam - Barman, Nivedita; Islary, Pungbili; Nayaka, Sanjeeva; Hoque, Raza Rafiqul; Daimari, Rebecca (Indian Forester, 2025)
Lichens are capable of growing on any substratum both natural and manmade. Tea plants serve as one such important substratum that supports growth of lichen. An attempt was made to understand the distribution of lichen diversity growing over nine tea gardens of Assam spatially distributed over three districts of Assam viz. Dibrugarh, Tinsukia and Sonitpur. A total of 71 species of lichen under 26 genera and 15 families were identified. It was dominated by crustose lichen (82%) followed by foliose and leprose lichen with 17% and 1% respectively. The family Graphidaceae comprising seven genera and 26 species emerged as the most dominant showing its luxuriant growth followed by Caliciaceae and Pyrenulaceae with 11 and nine species respectively. Among the genera, the tea gardens were mainly dominated by Graphis (15 species) followed by Pyrenula with nine species. The species, Dirinaria applanata, Graphis scripta and Trypethelium eluteriae were commonly found in all the districts. Of the three districts, highest number of lichen species was reported from Sonitpur with 59 species, while Tinsukia and Dibrugarh exhibited 18 and 7 species individually. The reason for a smaller number of lichen species in the other two districts is due to inadequate exploration of the regions for lichenology.